Performance indicators for benchmarking solar thermochemical fuel processes and reactors - Bulfin, Brendan (2022)
ABSTRACT: Concentrated solar energy offers a source for renewable high-temperature process heat that can be used to efficiently drive endothermic chemical processes, converting the entire spectrum of solar radiation into chemical energy. In particular, solar-driven thermochemical processes for the production of fuels include reforming of methane and other hydrocarbons, gasification of biomass, coal, and other carbonaceous feedstock, and metal oxide redox cycles for splitting H2O and CO2. A notable issue in the development of these processes and their associated solar reactors is the lack of consistent reporting methods for experimental demonstrations and modelling studies, which complicates the benchmarking of the corresponding technologies. In this work we formulate dimensionless performance indicators based on mass and energy balances of such reacting systems, namely: energy efficiency, conversion extent, selectivity, and yield. Examples are outlined for the generic processes mention above. We then provide guidelines for reporting on such processes and reactors and suggest performance benchmarking on four key criteria: energy efficiency, conversion extent, product selectivity, and performance stability.